Monitoring Ketinggian Air Sebagai Pendeteksi Banjir Menggunakan Notifikasi Telegram Berbasis Internet Of Things - Vindua, Raditia; Triaji, Hasmi Sya’Ban (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Floods are stagnant water caused by blocked rivers or rainfall. Currently residents estimate the potential for flooding is still done manually, there is no monitoring system for detecting water levels and flood warnings. There is no use of ultrasonic-based technology and telegram information notifications for monitoring water level levels as flood detectors. In this study the authors used data analysis methods consisting of observations, interviews and literature studies. The stages of designing a water level monitoring tool system as a flood detector using the Rapid Application Development (RAD) method consist of Requirements Analysis, Design Workshop (Modeling) and Implementation (Implementation). The purpose of this research is to make a water level monitoring tool as a flood detector using an ultrasonic sensor. Assisting online monitoring of water levels via smartphone telegrams as early information on flooding and increasing citizen awareness to detect water levels. The results of this study are that the water level monitoring tool for flood detection can detect the water level properly and can help minimize losses from the impact of flooding on residents by using this tool. The ultrasonic sensor provides accurate information about the water level distance. The buzzer sounds according to the expected distance and sound intensity. Telegram warning notifications provide monitoring information and water level warnings as flood detectors according to the specified water level settings. The mini water pump pumps standing water and drains the water to a safe place when the ultrasonic sensor detects that the distance has reached the maximum limit.